Hybrid ERC20 Ethereum Blockchain Multisignature Wallet 3of3 with Withdrawal Pattern, External Effects, and Mutex as Single Key and Reentrancy Mitigation. - Jason Al Hilal Sabda Dewa; Indra Waspada; Priyo Sidik Sasongko (Jurnal Masyarakat Informatika, 2024)
In the rapidly evolving era of Decentralized Finance (DeFi), the convergence of Blockchain technology with intermediary-free financial services has forged a revolutionary landscape. However, this progress has been accompanied by critical challenges, notably the Single Key Risk and reentrancy attack threats against ERC20 smart contracts in private Ethereum Blockchain. This research formulated a proactive approach and implemented an innovative solution by embodying Reliable Decentralized Finance through the deployment of a 3-of-3 Hybrid Multisignature Wallet system with Withdrawal Pattern, External Effects, and Mutual Exclusion in the form of a Decentralized Application (DApps). The system not only applied withdrawal patterns but also integrated external effects and the principle of mutual exclusion to enhance the security of smart contracts. The system development methodology was executed comprehensively using Agile Software Engineering, encompassing the development of both smart contracts and external applications (decentralized applications). Testing was conducted using Ganache EVM (Ethereum Virtual Machine) connected to the Hot Wallet Metamask as an Externally Owned Account (EOA) for transaction signing. Valid results were obtained from comprehensive testing against the system's functional requirements, affirming the system's success in managing Single Key Risk and preventing reentrancy attacks, providing a reliable and concrete solution